Afforestation of Urban Brownfields as a Nature-Based Solution. Experiences from a Project in Leipzig (Germany) - Dieter Rink; Catrin Schmidt (Land, 2021)
In Leipzig, despite strong growth, reurbanization and re-densification, in the last decade it has still been possible for the city to green brownfields with a new type of green space: urban forests. The background to this was of course the city’s decades of shrinkage and the emergence of numerous brownfields. The city of Leipzig started urban redevelopment in 2001 and pursued the strategy “more green, less density” in its planning. This included the creation of traditional and new green spaces as well as temporary uses. New green space concepts were also experimented with, including pocket forests and urban forests on larger, inner-city brownfields. This pursued several objectives: the forest was meant to contribute to improving the urban climatic and air-hygienic situation, to enhance the value of adjacent areas, create new recreational opportunities and contribute to increasing biodiversity. Another aspect is also the financing, for instance, the afforestation of brownfields is the cheapest way to create greenery. As a result of almost ten years of interdisciplinary monitoring of the project, it can now be stated that urban forests fulfil the objectives and are accepted and used by the population. Urban forests do not constitute an independent or new type of nature-based solutions they create new ecosystems from existing abandoned, brownfields, or neglected area.